Remaining Service Life Struktur Conveyor B pada Tambang Batubara PT XYZ di Kabupaten Banjar Provinsi Kalimantan Selatan - Roby Ardianta; Elfida Moralista; Zaenal (UNISBA Press, 2022)
Abstract. Conveyor is a mechanical device used to move material from one place to another. The structure of the conveyor is usually made of carbon steel which is subject to corrosion caused by the oxidation of the steel. Therefore, it is necessary to control corrosion in order to inhibit the corrosion rate so as to extend the Remaining Service Life (RSL). The method used in this research is thickness reduction by measuring using Ultrasonic Thicness Gauge TT 130, which is carried out on a conveyor structure that has a length of 90 meters and is divided into three segments consisting of 25 test points, and has a design life of 15 years with initial installation was in 2014 and was impregnated in 2020 with a nominal thickness of 13.00 mm and an actual thickness of 11.38 mm. The type of corrosion that occurs in the structure is uniform corrosion. The corrosion control method used is coating with a three layer system with primary coating using seaguard 5000 then intermediate coating using sherglass FF and top coating using aliphatic acrylic modified polyurethane. The value of the corrosion rate is 0.1833 to 0.32 mm/year which is classified into the good category, with a conveyor life of 6 years with a remaining service life of 7 to 11.5 years, of which 32% of the test points cannot reach the design life. Abstrak. Conveyor merupakan alat mekanis yang digunakan untuk memindahkan material dari satu tempat ke tempat lainnya. Struktur dari conveyor biasanya terbuat baja karbon yang pasti dapat mengalami korosi yang disebabkan oleh oksidasi yang dialami baja. Oleh karena itu diperlukannya pengendalian korosi agar dapat menghambat laju korosi sehingga dapat memperpanjang Remaining Service Life (RSL). Metode yang digunkan pada penelitian ini merupakan pengurangan ketebalan dengan melakukan pengukuran menggunakan Ultrasonic Thicness Gauge TT 130, yang dilakukan pada struktur conveyor yang memiliki panjang 90 meter dan di bagi menjadi tiga segmen yang terdiri atas 25 test point, serta memiliki umur desain selama 15 tahun dengan pemasangan awal pada tahun 2014 dan dilakukan impeksi pada tahun 2020 dengan tebal nominal 13,00 mm dan tebal aktual 11,38 mm. Jenis korosi yang terjadi pada struktur yaitu korosi merata. Metode pengendalian korosi yang dilakukan adalah coating dengan sistem three layer dengan primer coating menggunakan seaguard 5000 lalu intermediate coating menggunakan sherglass FF dan top coating menggunakan aliphatic acrylic modified polyurethane . Nilai dari laju korosi 0,1833 hingga 0,32 mm/tahun yang dimana terklasifikasikan kedalam katagori good, dengan umur pakai conveyor 6 tahun dengan sisa umur pakai berkisar 7 hingga 11,5 tahun yang dimana sebanyak 32% test point tidak dapat mencapai umur desainnya.